Revisiting Tide‐Induced Near‐Field Mixing in the Abyssal Ocean - Toshiyuki Hibiya; Yuki Tanaka; Taira Nagai; Yusuke Hirano (Geophysical Research Letters)
Abstract Vertical two‐dimensional numerical experiments incorporating Garrett‐Munk (GM) internal waves are conducted to investigate tide‐induced near‐field mixing over a finite‐amplitude sinusoidal seafloor, conventionally attributed to the breaking of high‐wavenumber internal tidal waves. Turbulent mixing is characterized by tidal excursion parameter (Te) and topographic steepness parameter (Sp) measuring tidal current strength and seafloor slope gradient, respectively. Under strong tidal currents (Te > 1), high‐wavenumber internal lee waves propagate upward from the seafloor. Even when Te and Sp are set to produce nearly the same upward energy flux, the vertical profile of mixing hotspots varies with Sp. For Sp ≳ 0.2, near‐inertial currents above the seafloor rapidly amplify by absorbing energy of internal lee waves from below, hindering their upward propagation and creating “short mixing hotspots.” For Sp < 0.2, these near‐inertial currents diminish, allowing internal lee waves to propagate upward and interact with the GM background internal waves, creating “tall mixing hotspots.”